KARAKTERISTIK BELAJAR SISWA TERISOLIR - TINI, WAR TINI (Universitas Negeri Padang, 2013)
Reality on the ground. The purpose of this study describe the characteristics of the isolated students, and describe the forms of services that can be provided by a guidance counselor in dealing with students who are isolated in the study. Types of qualitative research with qualitative research strategies Case Study Research (CSR) or case study, with interactive analysis with the findings reveal that.